2018
DOI: 10.1016/j.chemosphere.2018.05.082
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary record of plutonium in the North Yellow Sea and the response to catchment environmental changes of inflow rivers

Abstract: Plutonium (Pu) isotopes were first determined in surface and core sediment samples collected from the northern North Yellow Sea (NYS) to elucidate their source terms and deposition process as well as the response to catchment environmental changes of inflow rivers. Pu/Pu atom ratios in all sediments showed the typical global fallout value of ∼0.18 without any influences from the nuclear weapons tests conducted recently in the North Korea or early in the Pacific Proving Ground. The large variation of Pu activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…By comparison, the 240 Pu/ 239 Pu atom ratios in the surface sediments of the northern Yellow Sea range from 0.175 to 0.190, with an average of 0.184 ± 0.005. Besides, in two sediment cores of the northern Yellow Sea (NYSC-01, NYSC-02), the 240 Pu/ 239 Pu atom ratios vary from 0.163 to 0.233, with an average of 0.194 ± 0.02, which are relative constant and similar to those determined in the surface sediments (Xu et al 2018). Thus, it is clear that the atom ratios of 240 Pu/ 239 Pu obtained in these sediment samples of the northern Yellow Sea agree very well with the average value of ∼0.18 for global fallout.…”
Section: Methodssupporting
confidence: 65%
See 4 more Smart Citations
“…By comparison, the 240 Pu/ 239 Pu atom ratios in the surface sediments of the northern Yellow Sea range from 0.175 to 0.190, with an average of 0.184 ± 0.005. Besides, in two sediment cores of the northern Yellow Sea (NYSC-01, NYSC-02), the 240 Pu/ 239 Pu atom ratios vary from 0.163 to 0.233, with an average of 0.194 ± 0.02, which are relative constant and similar to those determined in the surface sediments (Xu et al 2018). Thus, it is clear that the atom ratios of 240 Pu/ 239 Pu obtained in these sediment samples of the northern Yellow Sea agree very well with the average value of ∼0.18 for global fallout.…”
Section: Methodssupporting
confidence: 65%
“…In the northern Yellow Sea, the distribution of 239+240 Pu activity in the surface sediments presents a westwards-increasing trend along the coast, and the highest value of 239+240 Pu activity appears near the northeast coast of Dalian Bay (Xu et al 2018). Chen et al (2013) have reported that after resuspension and transportation by the Liaonan Coastal Current, the Yalu River-derived fine-grained sediments are redeposited in water depths of 20-40 m, which is 180-300 km away from the Yalu River mouth and extends along the southeast coast of the Liaodong Peninsula between the northeast of Dalian Bay and southwest of the Changshan Islands.…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations